Absorption Characteristics of Cement Combination Concrete Containing Portland Cement, fly ash, and Metakaolin - Folagbade Samuel Olufemi (Institute of Research and Community Outreach - Petra Christian University, 2016)
The resistance to water penetration of cement combination concretes containing Portland cement (PC), fly ash (FA), and metakaolin (MK) have been investigated at different water/cement (w/c) ratios, 28-day strengths, and depths of water penetration using their material costs and embodied carbon-dioxide (eCO2) contents. Results revealed that, at equal w/c ratio, eCO2 content reduced with increasing content of FA and MK. MK contributed to the 28-day strengths more than FA. Compared with PC, FA reduced cost and increased the depth of water penetration, MK increased cost and reduced the depth of water penetration, and their ternary combinations become beneficial. At equal strengths and levels of resistance to water penetration, most of the cement combination concretes are more environmentally compatible and costlier than PC concrete. Only MK binary cement concretes with 10%MK content or more and ternary cement concretes at a total replacement level of 55% with 10%MK content or more have higher resistance to water penetration than PC concrete.